Letters On The Move: Erín Moure and Chus Pato’s Secession/Insecession and Nathanaël (Nathalie Stephens)’s Absence Where As (Claude Cahun and the Unopened Book) - Robichaud, Geneviève (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2016)
In this essay I examine the space for exchange and dialogue opened by Erín Moure’s translation of Chus Pato’s Secession, which in its Canadian edition is published alongside Insecession, Moure’s own response or reciprocation to Pato’s text. I also turn to Nathanaël’s (Nathalie Stephens) relationship to a photograph of Claude Cahun and to the claim that in Cahun the author resembles herself. I argue that the eloquence of the inclination in both works, as each stages translation as a form of correspondence, suggests a failure of reciprocity and equivalences that denies the giving-over of one text to the other. Moure and Nathanaël thus underscore translation as a privileged site for reflecting on translation as a relationship text.